(untitled) (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract Title: Economic Diplomacy in a Changing World: Between U.S. Hegemony and the Rise of Asian Partnerships. In the twenty-first century, global power structures have shifted from military confrontation to economic interdependence, making economic diplomacy a central instrument of statecraft. Economic diplomacy refers to the strategic use of trade, investment, aid, and financial instruments to achieve political goals and influence international relations. The United States has historically dominated this field since the Bretton Woods system, leveraging the dollar’s supremacy and international institutions to sustain its global hegemony. However, recent developments — including the 2008 financial crisis, the technological revolution, and the rapid rise of Asian economies — have gradually undermined the foundations of U.S. dominance. This paper explores how Washington reconfigures its economic diplomacy through sanctions, financial leverage, and the reorganization of global supply chains, while Asian powers, led by China, India, and Japan, pursue alternative paths through developmental and regional diplomacy. Initiatives such as the Belt and Road Initiative (BRI), the Regional Comprehensive Economic Partnership (RCEP), and BRICS+ illustrate Asia’s growing role in shaping a more multipolar economic order. Using an analytical–descriptive approach, the study argues that the current phase of international relations is characterized by the coexistence of competing models of economic diplomacy: the coercive and institutionalized U.S. model versus the cooperative and developmental Asian model. The findings suggest a transition toward a plural and network-based diplomatic system, where global influence is increasingly determined by economic connectivity rather than unilateral dominance. Keywords: Economic Diplomacy, U.S. Hegemony, Asian Partnerships, Global Governance, Belt and Road Initiative,.